2022
DOI: 10.2196/39068
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Patient Journey in Multiple Myeloma: Qualitative Review

Abstract: Background The patient experience of multiple myeloma (MM) is multifaceted and varies substantially between individuals. Current published information on the patient perspective and treatment of MM is limited, making it difficult to gain insights into patient needs regarding the condition. Objective In this review, a combined research method approach (ie, the review of published literature and social media posts) was undertaken to provide insight into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A recent review of several scientific studies and social media posts of patients with MM found that for both younger and older patients, it is important to them to be involved in the treatment decision-making process. 13 In another qualitative study of patients with MM and caregivers, they reported a substantial burden related to the intensive research needed to understand the evolving MM treatment landscape in order to participate in personalized treatment decisions. 14 Such intensive personal involvement impacted patient health and well-being, in addition to the treatment decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of several scientific studies and social media posts of patients with MM found that for both younger and older patients, it is important to them to be involved in the treatment decision-making process. 13 In another qualitative study of patients with MM and caregivers, they reported a substantial burden related to the intensive research needed to understand the evolving MM treatment landscape in order to participate in personalized treatment decisions. 14 Such intensive personal involvement impacted patient health and well-being, in addition to the treatment decision-making process.…”
Section: Discussionmentioning
confidence: 99%